The Researcher and the Real World: Problems in Interpersonal Communication - Losano, Wayne A. (Journal of Technical Writing and Communication, 1979)
The research scientist has been viewed by creators of popular film and fiction as a superspecialist with little ability to relate to the real world. Although this popular image of the researcher is exaggerated, real problems do exist for the researcher in his efforts to ommunicate with nonresearchers. The individuality, pioneering spirit, intensity, and dedication of the researcher serve to isolate him from the rest of society. The abstract nature of scientific research and the lack of a clearly definable product of much scientific research further disrupt communication between the researcher and the nonresearcher.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC9mNmpoLThscWItaGcyci1xdWYz